Differential Regulation of NF-κB and Nrf2 by Bojungikki-Tang Is Associated with Suppressing Lung Inflammation. (30th January 2018) - Park, Soo Ryun; Kim, Kyun Ha; Kwun, Min Jung; Lee, Ji Yeon; Won, Ran; Han, Chang Woo; Choi, Jun Yong; Joo, Myungsoo
Abstract : Bojungikki-tang (BT), an Asian herbal remedy, has been prescribed to increase the vitality of debilitated patients. Since a compromised, weakened vitality often leads to illness, BT has been widely used to treat various diseases. However, little is known about the mechanism by which BT exerts its effect. Given that BT ameliorates inflammatory pulmonary diseases including acute lung injury (ALI), we investigated whether BT regulates the function of key inflammatory factors such as NF- κ B and Nrf2, contributing to suppressing inflammation. Results show that BT interrupted the nuclear localization of NF- κ B and suppressed the expression of the NF- κ B-dependent genes in RAW 264.7 cells. In similar experiments, BT induced the nuclear localization of Nrf2 and the expression of the Nrf2-dependent genes. In a lipopolysaccharide-induced ALI mouse model, a single intratracheal administration of BT to mouse lungs ameliorated alveolar structure and suppressed the expression of proinflammatory cytokine genes and neutrophil infiltration to mouse lungs. Therefore, our findings suggest that suppression of NF- κ B and activation of Nrf2, by which BT suppresses inflammation, are ways for BT to exert its effect.